Incidence and mortality of cervical cancer in Latin America - Arrossi Silvina; Sankaranarayanan Rengaswamy; Parkin Donald Maxwell (Instituto Nacional de Salud Pública, 2003)
Cervical cancer incidence and mortality estimates for 2000 are presented for the 21 Latin American countries, using estimates from the statistical package GLOBOCAN 2000. Additional data on time-trends are also presented, using the WHO mortality database. By the year 2000, some 76 000 cervical cancer and almost 30 000 deaths were estimated for the whole region, which represent 16% and 13% of the world burden, respectively. Thus, Latin American countries are among those with highest incidence rates in the world, together with countries from Sub-Saharan Africa, South and South East Asia. Variation in incidence among countries is large. Very high rates are found in Haiti (ASR 93.9 per 100 000), Nicaragua (ASR 61.1 per 100 000) and Bolivia (ASR 58.1 per 100 000). It seems unlikely that differences in risks in the region can be explained as the result of screening activities. Several descriptive studies carried out to evaluate the screening programmes in Latin America have pointed out problems related to insufficient coverage and frequency of screening. Other related problems include inadequate collection and reading of cytological samplings as well as incomplete follow-up of women after the test. The main challenge for Latin America countries remains on how to organize effective screening programmes, and for this, a real and urgent commitment from public health services and decision-makers in the region is needed.